Model of color perception based image engineering and psychological impacts - Ситнянських, Л.М.; Ситник, О.Г. (Proceedings of National Aviation University (archive), 2009)
Handling a problems of influence of color sensing factors to a functionality of complicated systems of avionics and estimation test specialty as also their impact on quality of functionality is requiring of explanation of number of theoretical aspects. Ostent of color sensing markers on functionality of complicated systems of avionics and estimation test specialty are caused by impossibility of the decision of the problems of an optimality of processes of development, designing, operation, servicing or repair with help of firmware for image processingin dimension of CALS-technologies and without the benefit of developed theory of visualization of modern research.